The Spontaneously Fields and Wave Propagation Providing the Possible Self-Sourced Variations and the Most Elementary Structures: The Inflective Photon, the Vortex Photon, and the Sourced Photon with the Torsionally Inflective Spaces and Coordinates - Sengor, T. (IEEE, 2024)
The torsionally inflective coordinate systems family is developed. The wave propagation is evaluated in the torsionally inflective circularly cylindrical coordinate system. The topic is applied for developing the sub structures in the photon. The sub structure is configured with three infinitesimal torsional inflectors join at their common inflective points in a photon. The flows are calculated with the paths of sub structures for a photon from the canonically leading equations of motion with the modifications for the time energy.
Keywords: POINTS; Engineering; Remote Sensing; Optics; Telecommunications